Home spirometry utilisation in telemedicine clinic for cystic fibrosis care during COVID-19 pandemic: a quality improvement process - Heather Bruschwein; Martina Compton; Rhonda List; Elissa Starheim; Lindsay Somerville; Lauren Williamson; Rachel Murray; Deirdre Jennings; Dana Albon (BMJ Open Quality)
Aim The specific aims of this quality improvement (QI) project were to increase the percentage of eligible adult CF patients who owned an HSs from 37% to 85% and to increase the percentage of adult CF patients seen at UVA with available spirometry in telemedicine from 50% to 95% by 31 December 2020.Methods Following the Model for Improvement QI methodology, a standardised process was developed for monitoring forced expiratory volume in 1 s with HS during multidisciplinary telemedicine visits during the COVID-19 pandemic.Intervention (1) HSs were distributed to eligible patients and (2) Home spirometry was monitored in eligible patients with each telemedicine visit and results were used for clinical care decisions.Results Both specific aims were achieved ahead of expected date. In March 2020, the beginning of the pandemic, 37% (49/131) of patients owned an HS and 50% (9/18) of patients seen via telemedicine performed spirometry at home. By September 2020, 97% (127/131) of adult patients at UVA owned an HS and by October 2020, 96% (24/25) of patients provided spirometry results during their telemedicine encounters.Conclusion Employing QI tools to standardise the process of monitoring spirometry data with home devices via telemedicine is reliable and sustainable and can be replicated across centres that provide care for patients with CF.